The contemporary approach and new trends in the management of fibromyalgia (Research, Society and Development, 2024)
Introduction: Fibromyalgia is a chronic condition characterized by diffuse musculoskeletal pain and a series of symptoms such as fatigue, sleep disorders and cognitive problems, and is responsible for affecting and compromising various areas of the lives of affected patients. Objective: This integrative literature review aimed to gather general information on fibromyalgia and the new ways of approaching this disease. Materials and Methods: This study is defined as an integrative literature review on the general clinical characteristics of fibromyalgia and the ways of approaching it. The PICO strategy was used to develop a guiding question. Furthermore, the descriptors “Fibromyalgia”; “Management”; “Propaedeutics” were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The articles showed that fibromyalgia is a disease that compromises several areas of the patient's life. It was also established that its etiopathology is multifactorial, with a major genetic influence on symptom manifestations. Conclusion: In this context, fibromyalgia is a chronic rheumatological disease that has no cure. Diagnosis is eminently clinical and complemented by laboratory tests. Treatment today involves pharmacological and non-pharmacological measures, and an individualized therapeutic plan should be drawn up for each patient in order to improve their prognosis.